1999
DOI: 10.1034/j.1600-0420.1999.770305.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up study of human corneal endothelial cells, photographed in vivo before enucleation and 20 years later in grafts

Abstract: ABSTRACT.Purpose: To evaluate the long-term (20-year) survival of transplanted human corneal endothelial cells. Methods: The donor endothelium had been photographed 20 years ago with a specular microscope both before enucleation in the melanomatous eye and in situ after keratoplasty. The same donor endothelial cells were now photographed again 20 years later with a modern specular microscope to ascertain the morphology and cell density of the grafts. Results: In the earlier study the mean postoperative endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…Ruusuvaara (, ); Vasara et al. ) showed in his studies great disparities between the endothelial cell densities of the graft and the recipient cornea. After the transplantation, endothelial cell density decreased more rapidly in the graft than in the recipient cornea.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Ruusuvaara (, ); Vasara et al. ) showed in his studies great disparities between the endothelial cell densities of the graft and the recipient cornea. After the transplantation, endothelial cell density decreased more rapidly in the graft than in the recipient cornea.…”
Section: Introductionsupporting
confidence: 56%
“…Previously, we have found clear grafts with cell densities of only 500 cells/mm 2 (Ruusuvaara & Set€ al€ a 1988a,b). Ruusuvaara (1979Ruusuvaara ( , 1980; Vasara et al 1999) showed in his studies great disparities between the endothelial cell densities of the graft and the recipient cornea. After the transplantation, endothelial cell density decreased more rapidly in the graft than in the recipient cornea.…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, up to 30% of all donor corneas are discarded for excessive endothelium cell loss during storage (Means et al, 1995;Jones et al, 2009). Moreover, after corneal transplantation 48% of ECs die during the first year after corneal grafting (Ruusuvaara and Setala, 1988), a rate that exceeds 60% after 20 years (Vasara et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…EC loss during storage is the principal reason for up to 30% of all discarded tissue by tissue banks 4,6 . After transplantation, there is considerable and progressive EC loss 7,8 ; indeed, EC failure contributes to at least 25% of all failed grafts 15 years post-transplantation 9 .…”
Section: Introductionmentioning
confidence: 99%